Structuring effects of lecithins on model fat systems: A comparison between native and hydrolyzed forms. (October 2016) - Delacharlerie, S.; Petrut, R.; Deckers, S.; Flöter, E.; Blecker, C.; Danthine, S.
Abstract: Lecithin find a wide spread application in the food industry. The purpose of the work reported here was to systematically map the effects of some commercially available lecithins from different sources (soybean, sunflower, rapeseed), in their native state or hydrolysed form, on the crystallization behavior of model fat systems. To this end, systems based on palm oil as hard fat were studied. Next to macroscopic properties such as product hardness, the crystallization behaviour and the microstructure were studied as a function of time and temperature. Addition of the studied lecithin preparations had a significant influence on the hardness (p < 0.05) indicating a structuring effect; this was confirmed by polarised light microscopy and powder X-ray diffraction. The impact of the hydrolysed lecithin was however different from the native one. It was shown that the lecithin hydrophobicity is determinant for the structuring ability. Highlights: Addition of all the lecithins has a significant influence on the hardness. Lecithin influence the crystal morphology and polymorphic stability. The lecithin hydrophobicity is determinant for the structuring ability.